DESIGN OF STANDARD OPERATING PROCEDURES (SOP) AND IMPLEMENTATION AT PT BSP - Prila Anjani; Shinta Wahyu Hati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
This study aims to design a Standard Operating Procedure (SOP) for shipping companies in PT Bintan Samudra Pacific. The administration is an instruction that becomes an important factor in the success of a shipping company to control transportation operations. PT BSP which requires a Standard Operating Procedure (SOP) flow which is expected to be a reference and guide in conducting administrative activities that can facilitate the management of data related to the division of marketing administration, personnel administration, and financial administration. The method used in the design of SOPs is made by summarizing and analyzing several data obtained from data collection and evaluating business processes that have been carried out. From this research, SOP administration in shipping, marketing, personnel, and financial administration can be used as a guide in data management integrated.